Antioxidant Activity Test of Bride's Tears (Antigonon leptopus) Leaves Using the DPPH Method - Nailil Wafiq Azizah; Majidah Ramadan; Faisal Faisal; Devana Rahma Aldina; Ramadina Novia Putri; Nur Laila Anggraini; Sabilatul Mufarrohah; Satria Gemilang; Firadika Fitriansyah; Hosiyah Hosiyah; Nuvia Harini Wulan Suci; Nihlatus Sofiya; Terra Januarista; Ramizard Rafsanjani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Bridal tear leaves can be used to treat various health and beauty problems because they contain various active compounds, such as flavonoids, saponins, and tannins. These compounds have antioxidant, anti-inflammatory, and antibacterial properties. This flower contains antioxidants that can help protect the skin from damage caused by free radicals. This research aims to see the effectiveness of antioxidants from bridal tear leaves. The research method involves leaf extraction using 96% ethanol and testing antioxidant activity using the DPPH method. The research results showed that the extract sample from bride's tear leaves was (IC50 – 69.7146 ug/mL). This shows that the bride's tear leaf extract is quite strong in inhibiting free radical reactions.